Health behavior in Russia during the COVID-19 pandemic - Peshkovskaya, Anastasia; Galkin, Stanislav (Frontiers in Public Health, 2023)
In this article we report results from a nationwide survey on pandemic-related health behavior in Russia. 2,771 respondents aged 18 to 82 were interviewed between January 21 and March 3, 2021. The survey included questions on perceived vulnerability to coronavirus, prevention-related health behavior, readiness for vaccination, and general awareness about COVID-19. Descriptive data showed that 21.2% of respondents reported high vulnerability to the coronavirus, and 25% expressed fear. 38.7% of the surveyed individuals reported low trust in vaccination efficacy, 57.5% were unwilling to take a vaccine, which was much higher than official data. Based on the evidence obtained, four types of health behavior during the pandemic were constructed. Rational (29.3%) and denying (28.6%) behaviors prevailed in men, while women were found to more likely behave with vaccine hesitant demeanor (35.7%). Educational background affected the proportion of respondents with denying type of health behavior, who were also of younger age. Rational behavioral type was found to be more common in respondents aged above 50 years and prevailed as well among individuals with university degrees. Middle-aged population of Russia was highly compliant with prevention-related health practices; however vaccine hesitancy were also high among them. Furthermore, health behaviors varied significantly across Federal Districts of Russia. We convinced that our results contribute to existing public health practices and may improve communication campaigns to cause positive health behaviors.